At Westonci.ca, we provide reliable answers to your questions from a community of experts. Start exploring today! Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
Let's determine whether each function is even, odd, or neither.
### 1. [tex]\( f(x) = \sqrt{x^2} - 9 \)[/tex]:
1. Rewrite the function:
[tex]\[ f(x) = |x| - 9 \][/tex]
2. Test for evenness: A function [tex]\( f(x) \)[/tex] is even if [tex]\( f(x) = f(-x) \)[/tex].
[tex]\[ f(-x) = | -x | - 9 = |x| - 9 = f(x) \][/tex]
Since [tex]\( f(x) = f(-x) \)[/tex], the function [tex]\( f(x) = \sqrt{x^2} - 9 \)[/tex] is even.
### 2. [tex]\( g(x) = |x - 3| \)[/tex]:
1. Test for evenness:
[tex]\[ g(x) = |x - 3| \][/tex]
[tex]\[ g(-x) = |-x - 3| \][/tex]
2. Compare [tex]\( g(x) \)[/tex] and [tex]\( g(-x) \)[/tex]:
In general, [tex]\(|x - 3| \neq |-x - 3|\)[/tex], unless [tex]\( x = 3 \)[/tex] or [tex]\( x = -3 \)[/tex]
Since [tex]\( g(x) \neq g(-x) \)[/tex], this function is not even.
3. Test for oddness: A function [tex]\( g(x) \)[/tex] is odd if [tex]\( g(x) = -g(-x) \)[/tex].
[tex]\[ -g(-x) = -|-x - 3| \][/tex]
In general, [tex]\( |x - 3| \neq -|-x - 3| \)[/tex]
Since [tex]\( g(x) \neq -g(-x) \)[/tex] either, the function [tex]\( g(x) = |x - 3| \)[/tex] is neither even nor odd.
### 3. [tex]\( f(x) = \frac{x}{x^2 - 1} \)[/tex]:
1. Test for evenness:
[tex]\[ f(-x) = \frac{-x}{(-x)^2 - 1} = \frac{-x}{x^2 - 1} \][/tex]
Compare [tex]\( f(x) \)[/tex] and [tex]\( f(-x) \)[/tex]:
[tex]\[ f(-x) = -f(x) \][/tex]
Since [tex]\( f(x) \neq f(-x) \)[/tex], this function is not even.
2. Test for oddness:
[tex]\[ f(-x) = -f(x) \][/tex]
Since [tex]\( f(x) = -f(-x) \)[/tex], the function [tex]\( f(x) = \frac{x}{x^2 - 1} \)[/tex] is odd.
### 4. [tex]\( g(x) = x + x^2 \)[/tex]:
1. Test for evenness:
[tex]\[ g(x) = x + x^2 \][/tex]
[tex]\[ g(-x) = -x + (-x)^2 = -x + x^2 \][/tex]
Compare [tex]\( g(x) \)[/tex] and [tex]\( g(-x) \)[/tex]:
[tex]\[ g(x) = x + x^2 \neq -x + x^2 = g(-x) \][/tex]
Since [tex]\( g(x) \neq g(-x) \)[/tex], the function is not even.
2. Test for oddness:
[tex]\[ g(x) = x + x^2 \][/tex]
[tex]\[ -g(-x) = -(-x + x^2) = x - x^2 \][/tex]
Compare [tex]\( g(x) \)[/tex] and [tex]\( -g(-x) \)[/tex]:
[tex]\[ x + x^2 \neq -(-x + x^2) = x - x^2 \][/tex]
Since [tex]\( g(x) \neq -g(-x) \)[/tex], the function [tex]\( g(x) = x + x^2 \)[/tex] is neither even nor odd.
### Final Results:
- [tex]\( f(x) = \sqrt{x^2} - 9 \)[/tex] is even.
- [tex]\( g(x) = |x - 3| \)[/tex] is neither.
- [tex]\( f(x) = \frac{x}{x^2 - 1} \)[/tex] is odd.
- [tex]\( g(x) = x + x^2 \)[/tex] is neither.
### 1. [tex]\( f(x) = \sqrt{x^2} - 9 \)[/tex]:
1. Rewrite the function:
[tex]\[ f(x) = |x| - 9 \][/tex]
2. Test for evenness: A function [tex]\( f(x) \)[/tex] is even if [tex]\( f(x) = f(-x) \)[/tex].
[tex]\[ f(-x) = | -x | - 9 = |x| - 9 = f(x) \][/tex]
Since [tex]\( f(x) = f(-x) \)[/tex], the function [tex]\( f(x) = \sqrt{x^2} - 9 \)[/tex] is even.
### 2. [tex]\( g(x) = |x - 3| \)[/tex]:
1. Test for evenness:
[tex]\[ g(x) = |x - 3| \][/tex]
[tex]\[ g(-x) = |-x - 3| \][/tex]
2. Compare [tex]\( g(x) \)[/tex] and [tex]\( g(-x) \)[/tex]:
In general, [tex]\(|x - 3| \neq |-x - 3|\)[/tex], unless [tex]\( x = 3 \)[/tex] or [tex]\( x = -3 \)[/tex]
Since [tex]\( g(x) \neq g(-x) \)[/tex], this function is not even.
3. Test for oddness: A function [tex]\( g(x) \)[/tex] is odd if [tex]\( g(x) = -g(-x) \)[/tex].
[tex]\[ -g(-x) = -|-x - 3| \][/tex]
In general, [tex]\( |x - 3| \neq -|-x - 3| \)[/tex]
Since [tex]\( g(x) \neq -g(-x) \)[/tex] either, the function [tex]\( g(x) = |x - 3| \)[/tex] is neither even nor odd.
### 3. [tex]\( f(x) = \frac{x}{x^2 - 1} \)[/tex]:
1. Test for evenness:
[tex]\[ f(-x) = \frac{-x}{(-x)^2 - 1} = \frac{-x}{x^2 - 1} \][/tex]
Compare [tex]\( f(x) \)[/tex] and [tex]\( f(-x) \)[/tex]:
[tex]\[ f(-x) = -f(x) \][/tex]
Since [tex]\( f(x) \neq f(-x) \)[/tex], this function is not even.
2. Test for oddness:
[tex]\[ f(-x) = -f(x) \][/tex]
Since [tex]\( f(x) = -f(-x) \)[/tex], the function [tex]\( f(x) = \frac{x}{x^2 - 1} \)[/tex] is odd.
### 4. [tex]\( g(x) = x + x^2 \)[/tex]:
1. Test for evenness:
[tex]\[ g(x) = x + x^2 \][/tex]
[tex]\[ g(-x) = -x + (-x)^2 = -x + x^2 \][/tex]
Compare [tex]\( g(x) \)[/tex] and [tex]\( g(-x) \)[/tex]:
[tex]\[ g(x) = x + x^2 \neq -x + x^2 = g(-x) \][/tex]
Since [tex]\( g(x) \neq g(-x) \)[/tex], the function is not even.
2. Test for oddness:
[tex]\[ g(x) = x + x^2 \][/tex]
[tex]\[ -g(-x) = -(-x + x^2) = x - x^2 \][/tex]
Compare [tex]\( g(x) \)[/tex] and [tex]\( -g(-x) \)[/tex]:
[tex]\[ x + x^2 \neq -(-x + x^2) = x - x^2 \][/tex]
Since [tex]\( g(x) \neq -g(-x) \)[/tex], the function [tex]\( g(x) = x + x^2 \)[/tex] is neither even nor odd.
### Final Results:
- [tex]\( f(x) = \sqrt{x^2} - 9 \)[/tex] is even.
- [tex]\( g(x) = |x - 3| \)[/tex] is neither.
- [tex]\( f(x) = \frac{x}{x^2 - 1} \)[/tex] is odd.
- [tex]\( g(x) = x + x^2 \)[/tex] is neither.
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.